Optimal lengths for DNAs encapsidated by Epstein-Barr virus. - Bloss, T A (1994)
We measured the efficiency of DNA packaging by Epstein-Barr virus (EBV) as a function of the length of the DNA being packaged. Plasmids that contain oriP (the origin of latent EBV DNA replication), oriLyt (the origin of lytic EBV DNA replication), the viral terminal repeats (necessary for cleavage and packaging by EBV), and various lengths of bacteriophage lambda DNA were introduced into EBV-positive cells. Upon induction of the resident EBV's lytic phase, introduced plasmids replicated as concatemers and were packaged. Plasmid-derived concatemers of DNA with certain lengths were found to predominate in isolated virion particles. We measured the distribution of lengths of plasmid concatemers found within cells supporting the lytic phase of the viral life cycle and found that this distribution differed from the distribution of lengths of concatemers found in mature virion particles. This finding indicates that the DNA packaged into mature virions represents a selected subset of those present in the cell during packaging. These observations together indicate that the length of DNA affects the efficiency with which that DNA is packaged by EBV. Finally, we measured the length of the packaged B95-8 viral DNA and found it to be approximately 165 kbp, or 10 kbp shorter than the originally predicted size for B95-8 based on its sequence. Together with the results of other studies, these findings indicate that the packaging of DNAs by EBV is dependent on two imprecisely recognized elements: the viral terminal repeats and the length of the DNA being packaged by the virus.